Biodegradable plastic modification from durian seed starch and shrimp chitosan with the addition of plasticiziers glycerol and polyglycerol using microwaves - Saud Salomo; Astri Devi Br Pakpahan; Dea Gracella Siagian; Grecy Kristina Tampubolon; Salsabila Afani; Eddiyanto Eddiyanto; Junifa Layla Sihombing (Jurnal Pendidikan Kimia (JPKim), 2021)
Plastic waste takes up to 450 years to decompose. These problems can be overcome by creating other alternatives, one of which is by using biodegradable plastic. Biodegradable plastics are plastics made from natural polymers that are easily degraded by microorganisms. This study aims to examine the effect of the amount of plasticizer on the length of the degradation process and the effect of using microwaves on the length of time for molding biodegradable plastic. This biodegradable plastic is made by combining durian seed starch, shrimp chitosan and plasticizers in the form of glycerol and polyglycerol with volume variations of 1 mL, 2 mL, 3 mL, 4 mL, and 5 mL. This polymerization was carried out using a microwave with a power of 100 watts for 60 minutes. The resulting biodegradable plastics were characterized using the FTIR test, the Mechanical Properties test, the Absorbency test, and the Biodegradation test to determine the quality of the biodegradable plastic. The results of this study indicate the greatest tensile strength value is 1.9768 MPa, the largest elongation value is 21.2772%, the smallest water absorption is 45.40% for 5 minutes, and the largest degraded mass is 0.908 grams for 7 days. Based on this research, it can be concluded that the use of polyglycerol can accelerate the plastic degradation process. In addition, the use of microwaves can speed up the molding time of biodegradable plastics.Keywords: Biodegradable plastic, Durian seed starch, Shrimp chitosan, Glycerol, Microwaves